TRIM21 and Fc-engineered antibodies: decoding its complex antibody binding mode with implications for viral neutralization - Reusch, Johannes; Franken, Linda Elise; Then, Jakob; Ringler, Philippe; Butzer, Joachim; Juroschek, Thomas; Klein, Christian; Schlothauer, Tilman; Larivière, Laurent (Frontiers in Immunology, 2024)
TRIM21 is a pivotal effector in the immune system, orchestrating antibody-mediated responses and modulating immune signaling. In this comprehensive study, we focus on the interaction of TRIM21 with Fc engineered antibodies and subsequent implications for viral neutralization. Through a series of analytical techniques, including biosensor assays, mass photometry, and electron microscopy, along with structure predictions, we unravel the intricate mechanisms governing the interplay between TRIM21 and antibodies. Our investigations reveal that the TRIM21 capacity to recognize, bind, and facilitate the proteasomal degradation of antibody-coated viruses is critically dependent on the affinity and avidity interplay of its interactions with antibody Fc regions. We suggest a novel binding mechanism, where TRIM21 binding to one Fc site results in the detachment of PRYSPRY from the coiled-coil domain, enhancing mobility due to its flexible linker, thereby facilitating the engagement of the second site, resulting in avidity due to bivalent engagement. These findings shed light on the dual role of TRIM21 in antiviral immunity, both in recognizing and directing viruses for intracellular degradation, and demonstrate its potential for therapeutic exploitation. The study advances our understanding of intracellular immune responses and opens new avenues for the development of antiviral strategies and innovation in tailored effector functions designed to leverage TRIM21s unique binding mode.